QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)

Indigenous Education Initiatives in Quebec - Martin, Cathy (Education and Vitality Forum, 2021)

Political Engagement of Indigenous Youth in Québec - Lopes-Luchak, Milla (Youth for Youth Québec (Y4Y Québec), 2021)
According to the 2016 census, 1.2% of Québec’s population is indigenous (Page 2017) and 27.3% of that population is between 15 and 34, or the youth (Statistics Canada 2017). So far, Québec has had two indigenous members of government and there are none occupying official chairs nowadays (National Assembly of Québec). There is an issue of underrepresentation that affects the present and future of indigenous youth.

Quebec Past and Present : 9th Colloquium on Quebec Studies / 9ème colloque sur les études québécoises - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2021)

Profil de la jeunesse anglophone de la Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Ce profil de la situation de la jeunesse anglophone de la Gaspésie et des Îles-de-la-Madeleine a été commandité par trois organisations communautaires : le Comité pour l’action sociale anglophone (CASA), le Conseil des Madelinot·e·s anglophones (CAMI) et Vision Gaspé-Percé Now. Des travaux de recherche-action fondés sur une approche participative et communautaire ont servi de base au développement de ce profil. Ce faisant, l’étude sur laquelle le présent document se fonde permet d’avoir un portrait des réalités propres à la jeunesse, développé par les jeunes elleux-mêmes; ceci permettra de travailler plus efficacement à la résolution des enjeux et des difficultés auxquels ils et elles font face dans les différentes communautés de la région. Une méthode d’approche mixte a ainsi été développée via la combinaison d’une enquête en ligne et de groupes de discussions sur des sujets liés à l’émigration, à l’éducation, à l’emploi, à la vie sociale, aux services, etc. Au total, 438 jeunes de 15 à 35 ans ont participé à l’enquête en ligne, et neuf groupes de discussion ont été instaurés sur un total de six communautés regroupant 82 jeunes.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people aged 15-35 filled out the survey and nine focus groups were held in a total of six communities with a total of 82 youth.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Éducation autochtone : Les deux rives du fleuve - Advisory Board on English Education (2017)
À l’échelle mondiale, la recherche rend compte du faible rendement scolaire des élèves de culture autochtone, mais aussi d’une tendance progressive à améliorer cette situation. La Commission de vérité et de réconciliation (CVR) du gouvernement canadien a donné l’impulsion nécessaire pour que les provinces examinent leurs pratiques, et la Commission de l’éducation en langue anglaise (CELA) félicite le ministre de l’Éducation, du Loisir et du Sport de prendre part à l’initiative. Les rapports de recherche et les médias font état de facteurs nombreux et divers qui entravent la réussite des enfants autochtones à l’école. Certains, comme l’éloignement et l’inaccessibilité des communautés, la rareté et le coût élevé de la nourriture, la pauvreté, les mauvaises conditions d’habitation et une infrastructure défaillante, débordent du cadre des solutions purement éducationnelles, mais ils n’en ont pas moins, en se combinant, de profonds effets sur les résultats scolaires. Il faut donc mobiliser les services sociaux et médicaux pour améliorer les conditions qui influent sur la réussite scolaire des élèves autochtones, ce qui, nous l’espérons, sera facilité au Québec par le Plan d’action gouvernemental en matière de développement social autochtone. Quoi qu’il en soit, l’éducation reste à la base de toute solution potentielle aux difficultés et aux problèmes de cette population. Pour améliorer la situation des 100 000 Autochtones du Québec, il faut commencer par la jeune génération. D’ailleurs, bon nombre des problèmes qui mènent à l’insuccès scolaire, dont quelques uns sont abordés dans ce mémoire, peuvent être résolus par le système d’éducation. Il n’est pas question ici de prescrire un « remède aux problèmes » du système scolaire autochtone, aussi ce mémoire ne formule‑t-il pas de recommandations, à la différence de la plupart de ceux que la CELA a déposés jusqu’ici. Il dresse plutôt une liste des éléments qui peuvent alimenter la discussion sur l’éducation des Autochtones au Québec. Nous espérons en outre que certaines des observations et recommandations formulées dans nos mémoires précédents au sujet du système d’éducation anglophone seront d’un apport utile, même si notre perspective est surtout celle des différences entre cultures et des problèmes de longue date des systèmes scolaires autochtones.

Indigenous Education : Walking on Both Sides of the River - Advisory Board on English Education (2017)
Worldwide research has identified low school achievement levels among students from Indigenous cultures and there is a gradual movement to improve their situation. The Truth and Reconciliation Commission (TRC) of the Canadian government has provided the impetus for the provinces to examine their practices and the Advisory Board on English Education (ABEE) congratulates the Minister of Education, Recreation and Sports for joining this initiative. The research literature and the media have identified a broad range of issues affecting the success of Indigenous children in schools. Some of these issues, such as the remoteness and inaccessibility of the communities, poverty, the scarcity and high cost of food, poor housing, and infrastructure problems, are outside the scope of educational solutions, although they combine to have a profound effect on educational outcomes. Social and medical services must be called upon to improve the circumstances that contribute to the educational success of Indigenous students, and we hope this will be facilitated in Québec by the provincial government’s Aboriginal Social Development Action Plan. Yet education is fundamental to any potential solution to Indigenous concerns and problems, and any changes to the situation of the 100 000 Indigenous people of Québec must start with the younger generation. Many of the issues affecting the students and their success or failure in school can be addressed by the school system and this brief will identify some of them. In no way is this brief a prescription to “cure problems” in the Indigenous school system, so it does not contain recommendations, unlike most ABEE briefs. Rather, we will identify some of the issues that might contribute to the discussion of Indigenous education in Québec. We hope that some of the observations and recommendations we have made in earlier briefs regarding the Anglophone school system will be useful additions to the conversation, even though our perspective is influenced by differences between cultures and long-standing problems within Indigenous school systems.

Children 0 to 5 and their Parents : RTS des Terres-Cries-de-la-Baie-James - Community Health and Social Services Network (CHSSN) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

Resolution 2015-02: History of Residential Schools - Quebec Federation of Home and School Associations (QFHSA) (2015)

Résolution 2015-02 : L'histoire des Pensionnats - Quebec Federation of Home and School Associations (QFHSA) (2015)

David Hodges Embarks on N'we Jinan Community Tour - Quebec Community Groups Network (QCGN) (2014)

Lower North Shore Heritage Workbook : Following in the Footsteps of the Explorers - Anderson, Monica; Benoit, Kristina; Blattel, Adrienne; Cochrance, Candace (Coasters Association, 2008)
History is the study of past human events and activities. Studying history can help us better understand where we come from and therefore who we are as people. Historians have a lot in common with explorers, only they are traveling through time AND place. They hunt for clues about how people lived and acted in the past. To do this, they must use a lot of tools such as books, original documents, drawings and maps, and artefacts. They talk to people who might have lived through the time they are studying or who know stories handed down from that time. Some, like the movie character Indiana Jones, take a pick and shovel to dig in the earth to find answers to their question about the past. After they have found as much information as possible, they piece their story together and present it in books, museum exhibits, or documentaries. Being an historian takes patience and hard work but, like exploring, it can also be exciting to find out new things about olden times.

BCRC Newsletter - Black Community Resource Centre (BCRC) (2004)

Native Literacy Pre-school Education Project - The Centre for Literacy of Quebec (CFL) (The Centre for Literacy of Quebec (CFL), 1999)

Coasters Association Informer - Coasters Association (1996)

Coasters Association Informer - Coasters Association (1996)

Coasters Association Informer - Coasters Association (1996)

Coasters Association Informer - Coasters Association (1995)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1990)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1979)

Reaching the Rainbow: Aboriginal Literacy in Canada - Smith, Donna-Lee

Policy Brief : Mental Health and Suicide Prevention - Nunavik, Quebec - Youth for Youth Québec (Y4Y Québec)
In recent years, communities across Nunavik have received attention for other reasons than their young demographic: a growing suicide epidemic. In fact, remote and northern communities in Canada have consitently experienced the most significant effects of suicide in the country, with general incidence rates staggering at ten times the national average and as much as 24 times the national average (National Observer, 2019) for Inuit youth across Nunavik. Although there was a window between 2009 and 2013 when suicide was on the decline, the tendency has been consistently increasing for the past seven years (CBC, 2018).